2021
DOI: 10.1016/j.oooo.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Oral lesions in patients with SARS-CoV-2 infection: could the oral cavity be a target organ?

Abstract: Several viruses transmitted through saliva, such as herpes simplex virus, cytomegalovirus, and Zika virus, are capable of infecting and replicating in the oral mucosa, leading to painful oral ulcers. Few studies have described the oral manifestations of coronavirus disease 2019 (COVID-19). There is growing evidence that angiotensin-converting enzyme 2 (ACE2), the main host cell receptor of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is highly expressed on the epithelial cells of the tongue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
329
0
57

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(402 citation statements)
references
References 16 publications
16
329
0
57
Order By: Relevance
“…The documented manifestations of oral mucosa were quite heterogeneous, varying in the kind of lesion and the location. The most frequent findings were ulcerations ( 9 , 50 , 60 62 ), sometimes associated with necrotic areas ( 50 , 51 ), aphthous-like lesions ( 51 , 55 , 56 , 58 ), and petechiae ( 51 , 52 , 54 ). Maculae ( 53 , 60 ), blisters ( 10 , 57 ), lingual papillitis or depapillation ( 58 ), and erythema or red plaques ( 52 , 63 ) were also among the described oral lesions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The documented manifestations of oral mucosa were quite heterogeneous, varying in the kind of lesion and the location. The most frequent findings were ulcerations ( 9 , 50 , 60 62 ), sometimes associated with necrotic areas ( 50 , 51 ), aphthous-like lesions ( 51 , 55 , 56 , 58 ), and petechiae ( 51 , 52 , 54 ). Maculae ( 53 , 60 ), blisters ( 10 , 57 ), lingual papillitis or depapillation ( 58 ), and erythema or red plaques ( 52 , 63 ) were also among the described oral lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Tongue ( 9 , 51 , 54 , 55 , 58 62 ), lips ( 10 , 50 , 51 , 57 , 59 , 60 , 63 ) and palate ( 52 , 54 , 60 ) were the most frequently described anatomical locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of the oral lesions reported in the literature to be associated with COVID‐19 includes aphthous ulcers and vesicular ulcerations 7 . A report on oral necrotic ulcers and aphthous‐like ulcerations that developed after taste alteration and affected the tongue, lips, palate, and oropharynx was published recently 8 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that oral manifestations are commonly noticed in about 45% of COVID-19 patients [ 24 , 25 , 26 ]. Salivary glands, tonsils, and tongue are highly sensitive for SARS-CoV-2 infection [ 27 , 28 , 29 ]. The development of infection causes loss of taste, smell, and blisters on the tongue in COVID-19 patients [ 30 , 31 ].…”
Section: Mechanism Of Infection In Oral and Overall Body Healthmentioning
confidence: 99%